ENSURING HUMAN RIGHTS IN THE CONTEXT OF IMPLEMENTATION OF ELECTRONIC VOTING IN UKRAINE: PERSPECTIVES AND RISKS - Liudmyla Gudz (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право»)
Introduction. The article focuses on the advantages of e-voting and the insufficient study of human rights aspects in this process. Therefore, the purpose of the study is to identify public policy strategies for the successful implementation of e-voting in Ukraine, taking into account international experience and ensuring human rights and freedoms in the electoral process.